2018
DOI: 10.1038/s41559-018-0673-5
|View full text |Cite
|
Sign up to set email alerts
|

Shark genomes provide insights into elasmobranch evolution and the origin of vertebrates

Abstract: Sequencing the large genomes of sharks. We focused on the brownbanded bamboo shark Chiloscyllium punctatum, for which we recently tabled embryonic stages 8 , and the cloudy catshark Scyliorhinus torazame. Their whole genomes, measured to be approximately 4.7 and 6.7 Gbp, respectively, were sequenced de novo to obtain assemblies including megabase-long scaffolds (Supplementary Note 1.1). We also assembled the genome of the whale shark Rhincodon typus using short sequence reads previously generated 3 (Supplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
296
5
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 193 publications
(332 citation statements)
references
References 98 publications
21
296
5
2
Order By: Relevance
“…Undoubtedly, this line of research would benefit from sequencing the genomes of key elasmobranch species and detailed studies on the molecular mechanisms that underlie chondrichthyan electroreception. Currently, the genomic sequences are known for a handful of the nearly 1300 chondrichthyans including: the whale shark Rhincodon typus (Smith 1828) (Read et al, ), C. punctatum , cloudy catshark Scyliorhinus torazame (Tanaka 1908) (Hara et al, ) , white shark Carcharodon carcharias (Linnaeus 1758) (Marra et al, ) and elephant shark Callorhinchus milii (Bory de Saint‐Vincent 1823) (Venkatesh et al, ). Leucoraja erinacea is the nearest model elasmobranch species to date and the assembly of its genome is underway at http://www.skatebase.org (Wang et al, ).…”
Section: Summary and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Undoubtedly, this line of research would benefit from sequencing the genomes of key elasmobranch species and detailed studies on the molecular mechanisms that underlie chondrichthyan electroreception. Currently, the genomic sequences are known for a handful of the nearly 1300 chondrichthyans including: the whale shark Rhincodon typus (Smith 1828) (Read et al, ), C. punctatum , cloudy catshark Scyliorhinus torazame (Tanaka 1908) (Hara et al, ) , white shark Carcharodon carcharias (Linnaeus 1758) (Marra et al, ) and elephant shark Callorhinchus milii (Bory de Saint‐Vincent 1823) (Venkatesh et al, ). Leucoraja erinacea is the nearest model elasmobranch species to date and the assembly of its genome is underway at http://www.skatebase.org (Wang et al, ).…”
Section: Summary and Future Researchmentioning
confidence: 99%
“…Leucoraja erinacea is the nearest model elasmobranch species to date and the assembly of its genome is underway at http://www.skatebase.org (Wang et al, ). These genetic studies have shown that some benthic associated species have very few odorant receptor genes expressed in the olfactory epithelium (Hara et al, ; Venkatesh et al, ) and it is likely that further genomic screens could lead to insights about chondrichthyan electrosensory phenotypes.…”
Section: Summary and Future Researchmentioning
confidence: 99%
“…In our study, Hgf expression was detected throughout the pectoral fin buds, with intensified expression in the anterior and posterior parts. In fact, the orthologies of the Hgf and c‐Met genes analyzed for S. torazame (Adachi et al., ) and S. canicula (in this study) are suggested by their high cross‐species similarity (Supporting Information Figure ) and the small numbers of synonymous substitutions per site (0.081 and 0.019, respectively, compared with the inter‐order count of over 0.400) (Hara et al., ).…”
Section: Discussionmentioning
confidence: 56%
“…A recent study reported that in a different species in the genus Figure S1) and the small numbers of synonymous substitutions per site (0.081 and 0.019, respectively, compared with the inter-order count of over 0.400) (Hara et al, 2018).…”
Section: Discussionmentioning
confidence: 96%
“…The differential retention of genes could be seen as a stochastic process, in which the resulting differences in gene complement do not translate into functional consequences. This could be due to some functional redundancy among the paralogs that could work as a backup (i.e., functionally overlapping paralogues) in the case one is lost or inactivated (Albalat & Cañestro, 2016;Cañestro, Catchen, Rodriguez-Mari, Yokoi, & Postlethwait, 2009;Félix & Barkoulas, 2015), or a byproduct of divergent nature of the genomic location in which the duplicates are found (Hara, Takeuchi, et al, 2018;Hara, Yamaguchi, et al, 2018). Alternatively, it is also possible that the presence of multiples copies opens opportunities for the emergence of biological novelties (Force et al, 1999;Hughes, Hughes, Howell, & Nei, 1994;Ohno, 1970;Ohno, Wolf, & Atkin, 1968;Zhang, 2003).…”
Section: Gene Duplication and Gene Loss As Sources Of Evolutionary mentioning
confidence: 99%